Knowledge, Attitude and Practice of Exclusive Breast Feeding among Mothers: A case study of Sanepa Sachal, Lalitpur District - KC, Ganga (Patan Pragya, 2020)
Breastfeeding has been accepted as the most vital intervention for reducing infant mortality, ensuring optimal growth and development of children. Proper breastfeeding provides all essential nutrients for the first 6 months and is one of the cost effective intervention for reducing infant mortality and disease. It is one of the essential actions for infant development and survival. Maternal knowledge and attitudes as well as socio- demographic and cultural factors influence the practice of exclusive breastfeeding (EBF).This study reflects the knowledge, attitude and practice of EBF among breastfeeding mothers with infants aged 0-6 months. Exclusive breastfeeding means feeding a baby with only mother’s breast milk without any additional food or drinks including water. The main objective of this research is to explore the knowledge, attitude and practice of EBF behavior of the mothers. Using the simple random sampling, Sachal area, ward no.2 of Lalitpur metropolitan city was selected as study area. For the data collection 30-breastfeeding mother-infant pairs were purposively selected as the key informant. Data were collected from 30 mother-infant pairs by using interview schedules.